THE EFFECT OF THE ADDITION OF KECOMBRANG (NicolaiaspesiosaHoran) EXTRACT ON THE QUALITY OF SMOKED CATFISH SELAIS (Cryptopterusbicirchis) - Muhammad Hambali; Sukirno Mus; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was aimed to determine the effect of addition of kecombrang (Nicolaiaspeciosa Horan) extract at varied concentration on the quality of the smoked catfish selais (Crytopterusbicirchis). The research was used experimental method and composed as randomized block design (RBD). The treatment was addition of kecombrangextract into the fish meat at different concentration, consisting of 4 levels, namely: catfish selais without the addition of kecombrang extracts (K₀), catfish selais with addition of kecombrang extracts 3% (K3), catfish selais with addition of kecombrang extracts 6% (K6) and catfish selais with addition of kecombrang extracts of 9% (K9). The smoked catfish products then were stored for 0 days, 15 days, 30 days and 45 days at room temperature. The results showed that the different concentrations of the kecombrang extract solution highly significantly affected to the organoleptic value (appearance, taste, aroma and texture), moisture content, total phenol, total acid, pH, antioxidant activity of the smoked catfish produced, but significantly affected to the value of TBA. The highest quality of the smoked catfish was produced by the control treatment, which was without kecombrang added (K0) as indicated by the highest value of organoleptic characteristics. The smoked catfish selais was appeared intact, clean, brown, shiny specific types, smelt distinctive aroma of smoked fish, tasted good and tasty, and textured intact, clean, brown, shiny specific species. The smoked catfish contained water of 32.46%, total 1:15 ppm phenol, 4.73% total acid, pH 6.86, TBA 4.02mg/kg, and antioxidants 62.81%. Keywords: Crytopterusbicirchis, Nicolaiaspeciosa, kecombrang extract, smoked catfish